Three‐dimensional printing hydrogel scaffold with bioactivity and shape‐adaptability for potential application in irregular bone defect regeneration. Issue 35 (21st July 2022) - Wang, Jing; He, Meiling; Du, Meixuan; Zhu, Ce; Jiang, Yuling; Zhuang, Yi; Qi, Lin; Liu, Zheng; Li, Yubao; Liu, Limin; Feng, Ganjun; Wang, Danqing; et al.
Abstract: Complex shaped bone defects that need to be filled are very common in clinic. But after filling, gaps are inevitably left between substitutes and host bone due to the poor conformability of preformed implants, hence hindering bone regeneration. Therefore, based on our previous study, we here used the bioink (named PPG) composed of polyurethane, polyacrylamide, and gelatin with optimized composition ratio to three‐dimensionally (3D) print an inorganic/organic composite hydrogel scaffold with self‐expandability to fill irregular bone defects and bioactivity to accelerate bone healing through adjusting the content of bioactive ceramic (BC). The results indicated that, the 3D printed BC/PPG scaffold had a rough surface on each fiber; with the incorporation of BC powders, the composite hydrogel scaffolds in swelling experiments could perform a comparable self‐adaptability to PPG hydrogel scaffold; the bioactive ions including Ca, Mg, and Si could be released from the composite scaffold and induce the rapid deposition of bone‐like apatite. The mechanical tests proved that the BC(10%)/PPG scaffold was the top performer under compression. The in vitro cell assessment illustrated that compared with PPG hydrogel scaffold, the BC/PPG composite scaffolds were more favorable to the proliferation and spreading of bone mesenchymal stem cells (BMSCs). Abstract :